1985
DOI: 10.1111/j.1399-6576.1985.tb02178.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Haemodynamic Changes during Caesarean Section: A Comparison of Epidural and General Anaesthesia

Abstract: Haemodynamic measurements were performed on 20 healthy women before and during elective caesarean section under epidural (10 women) or general anaesthesia (10 women). The influence of the two anaesthetic techniques on the haemodynamic changes associated with operative delivery was compared. The following haemodynamic variables were studied: cardiac output (CO), stroke volume (SV) determined non-invasively with impedance cardiography, heart rate (HR), systolic (SBP) and diastolic blood pressure (DBP), pulse pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 19 publications
3
15
0
1
Order By: Relevance
“…The elevation in central venous pressure after infusion of 2 litres of crystalloid solution and establishment of epidural block lends support to this. 3 A decrease in systolic arterial blood pressure of greater than 20% occurred in 25% of subjects after epidural blockade. Previous studies, which have used a similar definition, have reported hypotension in 2 5 4 5 % of subjectsZ'i5'16 Lewis et d 3 suggested that the incidence of hypotension was related to the volume of preload administered.…”
Section: Discussionmentioning
confidence: 99%
“…The elevation in central venous pressure after infusion of 2 litres of crystalloid solution and establishment of epidural block lends support to this. 3 A decrease in systolic arterial blood pressure of greater than 20% occurred in 25% of subjects after epidural blockade. Previous studies, which have used a similar definition, have reported hypotension in 2 5 4 5 % of subjectsZ'i5'16 Lewis et d 3 suggested that the incidence of hypotension was related to the volume of preload administered.…”
Section: Discussionmentioning
confidence: 99%
“…8 The preference for epidural anaesthesia in this case was influenced by the desire to avoid the hypertensive response to tracheal intubation and the narcotics necessary to modify this. 8 The preference for epidural anaesthesia in this case was influenced by the desire to avoid the hypertensive response to tracheal intubation and the narcotics necessary to modify this.…”
Section: Discussionmentioning
confidence: 99%
“…8 The preference for epidural anaesthesia in this case was influenced by the desire to avoid the hypertensive response to tracheal intubation and the narcotics necessary to modify this. Epidural anaesthesia, utilising small increments of local anaesthetic to give the gradual onset of sympathetic blockade accompanied by adequate circulatory preload, and the use of small doses of ephedrine as required provides the necessary cardiovascular stability.…”
Section: Discussionmentioning
confidence: 99%